Design and synthesis of small molecules with difluoroquinoxaline units for OSCs. (2nd July 2020) - Kong, MinSung; Lee, Jihoon; Song, Suhee; Park, Seong Soo; Lee, Gun Dae; Lee, Won-Ki; Kim, Jin Young; Park, Sung Heum; Jin, Youngeup
Abstract: We designed and synthesized three novel small molecule donors (SM1, SM2 and SM3) that consist of thiophene as the electron-donating end group and 6, ​7-​difluoroquinoxaline moiety as a novel electron-withdrawing core group. The organic low band gap molecules with 6, ​7-​difluoroquinoxaline and thiophene units were synthesized using Stille coupling to generate SM1, SM2 and SM3. The absorption of SM2 and SM3 in solution was red shifted due to increased conjugation length of added thiophene units. In case of SM2 and SM3, introduction of hexyl chain in terminal thiophene units improve solubility in organic solvent. The maximum absorption peaks of SM1, SM2 and SM3 in solid thin films were at 482, 505 and 518 nm, respectively. SM3 was red shifted as compare to SM2 due to increased π-π stacking of electron donor materials.